Trade tensions in LAC: Modeling outcomes - Laborde Debucquet, David; Piñeiro, Valeria (International Food Policy Research Institute, 2019)
Trade tensions between the major world economies increased in 2018, and US tariff increases triggered reprisals and counter-reprisals. In Latin America and the Caribbean (LAC), trade tensions between the US and China and other US trade partners are expected to generate a mix of opportunities and threats for exporters of food products. To better understand the likely impacts of global trade tensions for LAC, we modeled a set of four scenarios using the MIRAGRODEP model1. We looked at impacts on exports, imports, production, GDP, household consumption, and adjustment costs through changes in labor markets up to 2030. Impacts will differ across the region’s highly heterogeneous countries, but some broad trends are evident.